Income Distribution and Convergence in the Transition Process - Jens Hölscher (Luxembourg Income Study (LIS), 2001)
The aim of this study is to clarify, whether and where the widespread opinion that systemic change from socialism to capitalism went along with dramatically rising inequality is true and how income distribution does affect the overall growth performance of transition countries. The countries under review are: the Czech Republic, Hungary, Poland, and Russia. The findings are analyzed against the background of convergence or divergence respectively vis-à-vis the European Union (EU) level of income and income distribution. Here Germany, being the neighboring country and biggest EU economy, is taken as benchmark. For the Czech Republic, Hungary and Poland it can be shown that income distribution remained relatively stable before and throughout the transition period on the basis of so far unpublished data from the Luxemburg Income Study database. Russia however displays a sharp increase in income distribution. These results are illustrated by Lorenz curves and underpinned by developments in functional income distribution and social transfers. An attempt is made to locate these transition countries on a stylized Kuznets curve and further qualitative factors referring to growth and equality are considered.
Keywords: 330; Einkommensverteilung; Übergangswirtschaft; Wirtschaftswachstum; Entwicklungskonvergenz; Vergleich; Tschechische Republik; Ungarn; Polen; Russland